216 Identifying a novel role for pmca1 (atp2b1) in heart rhythm instability. (5th June 2017) - Wilson, Claire; Cartwright, Elizabeth; Zi, Min; Li, Yatong
Abstract : Arrhythmias continue to be a leading cause of death and disability across the world, and genetics are one of the mechanisms that are known to increase susceptibility. By identifying new genetic influences and further understanding the pathways involved in heart rhythm control we can begin to tackle some of the main challenges facing treatment development. Here we aim to identify a new role for a gene linked to several features of heart failure Atp2b1 (Plasma membrane calcium ATPase 1, PMCA1). Along with its role in hypertension and other aspects of cardiac physiology, we believe PMCA1 may also influence heart rhythm stability and consequently the development of arrhythmias. To investigate the role of PMCA1 in cardiac rhythm, cardiomyocyte-specific knockout mice (PMCA1 CKOÃ, Â ) were generated. In vivo electrocardiography showed PMCA1 CKO displayed signs of cardiac repolarisation dysfunction related to prolonged QT and JT intervals. Supplementary analysis using Langendorff-perfused hearts revealed PMCA1 CKO hearts have prolonged action potential duration compared to controls. Additionally using the methods highlighted above, PMCA1 CKO mice were shown to have an increase arrhythmia susceptibility to both in vivo and ex vivo programmed electrical stimulation. Further echocardiography and histological analysis showed these heart rhythm abnormalities occur in the absence of detectable structural heart disease with PMCA1 CKO cardiac structure and function being comparable to controls. Our findings suggest a novel role for PMCA1 in heart rhythm stability, distinct from other cardiac disease. Furthermore, alterations in expression of Atp2b1 could influence an individuals susceptibility to developing arrhythmias.